Comparison of kinematics and kinetics between unassisted and assisted maximum speed sprinting - Gleadhill, S.; Jiménez-Reyes, P.; van den Tillaar, R.; Nagahara, R. (Journal of Sports Sciences, 2023)
Producing comparable/greater ground reaction forces (GRFs) at faster running speeds is beneficial for sprint performance, and assisted sprint training is used to induce faster running speed conditions. This study aimed to demonstrate the characteristics of assisted sprinting at the maximal speed phase and investigate acute differences to control sprinting. Fifteen sprinters completed control and assisted (5 kg) sprints over force platforms. Assisted sprinting increased running speed (9.3% mean difference), while propulsive mean force (-4.3%) and impulse (-12.4%) decreased, suggesting that running speed improvements were caused primarily by assisted pulling force rather than improvements in anteroposterior force production of athletes. In addition, vertical mean force increased (4.2%), probably due to braking mean force (34.2%) and impulse (32.5%) increases. Magnitude of control trial maximum speed was achieved earlier (during acceleration) in assisted trials, and net anteroposterior (includes both braking and propulsive components) mean force (67.2%) and impulse (67.9%) increased at this matched speed, suggesting that assisted sprints could be used to practice producing greater GRFs at comparable speeds. Running speed improvement by pulling force was associated with contact time decreases (r = -.565), suggesting that shortening contact time may be important for effective assisted sprinting.